Ribosomal DNA fingerprinting in the identification of non sporulating endophytes from Magnolia liliifera (Magnoliaceae) - Promputtha I. (2014)
The sporulating endophytic fungi isolated from Magnolia liliifera were identified to genus or species level using morphological characters. Non-sporulating isolates are generally termed as 'mycelia sterilia' and are grouped as 'morphospecies' based on similar cultural characters. Mycelia sterilia were grouped to 31 morphospecies and were further identified based on ribosomal DNA (rDNA) sequence analysis. The 5.8S gene, ITS1 and ITS2 regions of rDNA from all morphospecies were amplified and sequenced. Phylogenetic analysis indicated that MS88 were related to the genus Massarina (Lophiostomataceae), MS9, MS11 and MS47 to Xylaria (Xylariaceae), MS19 to Glomerella (Phyllachoraceae), MS25 to Hypoxylon (Xylariaceae), MS27 to Bionectria (Bionectriaceae) and the remaining 24 morphospecies were related to Phomopsis and Diaporthe (anamorphic Phomopsis).